Computer system for differential thermal analysis of low melting metals and alloys - Бабак, В. П.; Филоненко, С. Ф.; Прохоренко, C. B. (Proceedings of National Aviation University (archive), 2000)
Considered is a computer system for differential thermal analysis of low melting metals and |oys using registration and processing acoustic emission signals